Return to the homeland in desperate times: social imaginaries around those returned to Petare-Venezuela in time of pandemic - Gómez Castillo, Suzuky Margarita (2021)
The purpose of this research is to characterize the social imaginaries that emerge from the life stories, around the returnees to the El Carpintero de Petare sector in Miranda-Venezuela, the scene of the investigation, during the time of the pandemic. The present work is a type of qualitative research, from the interpretive paradigm with a biographical approach and narrative design, from the perspective of the life story. Among the theoretical postulates treated, it is worth mentioning; The imaginary institution of society (Castoriadis, 1993), Life History (Ferraroti, 2008) and Self-care deficit theory (Orem, 1991). Among the results, it is worth mentioning that public prevention policies against COVID-19 cannot be proposed under conditions that stigmatize and produce fear and suspicion in the community. This cannot be considered a productive way to control infections.